HTML 5 and CSS 3 : illustrated complete - Vodnik, Sasha (Illustrated series, 2011)
"Focused Lessons, each two-page spread focuses on a single skill, providing a guide for students as they complete the lesson. Concise steps, steps provide clear instructions for completing tasks, with action items in green boldface for emphasis to keep students on track. Illustrations, each lesson shows large illustrations of screens so students can compare their results as they complete key steps. Visual Design, keeps learners of all levels engagedand on track. Brand new book, provides coverage of basic to advanced concepts and skills for developing Web pages and Web sites using HTML5 and CSS3. Covers how to write and edit code using a basic text editor and browser. Focus on building sites, sample projects include professionally-designed layouts and Web-ready text, allowing users to focus on building the skills needed to combine these elements into web pages and web sites. Tested on multiple browsers, all code was tested on several widely used browsers; all steps can be completed using a Windows or Mac computer. Hot new topics, covers HTML5 semantic elements, downloadable fonts, multicolumn and fluid layouts, semantically accurate table layouts using CSS, and cross-browser code and strategies"-- Back of book